Effectivity Analysis of Offline and Online Learning Systems on Mendel’s Law of Inheritance Topic in High School Grade 11 Students - Addabiyah, Sayyidatul; Lisdiana, Lisa (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2024)
This research aims to compare the effectiveness of offline and online learning systems on inheritance topic in grade 11 high school students of MAS Kanjeng Sepuh in terms of student learning outcomes, student responses, and management of learning process. Online learning carried out by using the Whatsapp, Google Classroom and Google Meet applications, while offline learning was carried out face-to-face in the classroom. The design of this study used a Quasi Experimental Design with a Non-equivalent control group design type. This research was conducted at MAS Kanjeng Sepuh with a total of 24 students from class 11 IPA 1 and 11 IPA 2. The sampling technique used was saturation sampling. The results of the research showed that there were no significant differences in learning outcomes before and after online learning, but significant differences were found in learning outcomes before and after offline learning. Students showed more positive responses to the offline learning system than the online learning system. In addition, the management of learning process in online and offline learning was in the good and excellent categories so that they were equally effective. Therefore, it can be concluded that the offline learning system was more effective than the online learning system in terms of learning outcomes and student responses. Meanwhile, in term of the management of learning process, offline and online learning systems were equally effective. Both online and offline learning systems have their advantages and disadvantages that affect the effectiveness of learning, so more attention is needed to minimize the disadvantages of each learning system, especially online learning systems so that the learning process can be more optimal. Keywords: online learning, offline learning, learning outcomes, student responses, high school